Hoạt tính quang xúc tác của ZnO và Mn-ZnO được tổng hợp bằng phương pháp đốt cháy - Hương Huế, Hoàng Thị; Bảng, Nguyễn Đình; Ánh Nguyệt, Bùi Thị (Vietnam Journal of Chemistry, 2015)
In this work, manganese-doped and undoped ZnO photocatalysts were synthesized by the combustion method using polyvinyl alcohol as a fuel. The synthesized samples were characterized by using X-ray diffraction (XRD), energy dispersive X-ray (EDX) analysis and UV-Vis spectroscopy. The XRD spectra show that all the samples are hexagonal wurtzite structures. UV-Vis spectroscopy showed significant difference in the optical absorption of Mn-doped ZnO. Enhancement in optical absorption of Mn-doped ZnO indicates that it could be used as an efficient photocatalyst under visible light irradiation. The photo-reduction activities of photocatalysts were evaluated using a basic methylene blue as organic contaminant irradiated with visible light from 36 W compact bulb. It was found that Mn-doped ZnO bleaches methylene blue better than undoped ZnO upon its exposure to the visible light.